(untitled) (International journal of artificial intelligence, 2026)
This article examines the environmental issues of radioactive waste in the Republic of Uzbekistan, which was one of the main sources of mining and processing radioactive (uranium- and thorium-containing) ores for the former Soviet Union. The article also notes that waste from inactive uranium mining and processing plants, uranium mine tailings, and storage facilities are sources of radioactive contamination. It also notes that the environmental issues of radioactive waste include not only the threat it poses to public health and the environment, but also the significant resource requirements for its safe management.